An Efficient and Green Procedure for Synthesis of Pyrrole Derivatives by Paal–Knorr Condensation Using Sodium Dodecyl Sulfate in Aqueous Micellar. (4th March 2013) - Veisi, Hojat; Azadbakht, Reza; Ezadifar, Mehdi; Hemmati, Saba
Abstract : A simple, economical, and green approach to the synthesis of N ‐substituted pyrroles using sodium dodecyl sulfate as surfactant in water is described. The experiment protocol features simple operations, and the products are isolated in high to excellent yields (60–98%). Abstract :